2018
DOI: 10.1002/jsfa.9090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxidative stability and protein profile of flaxseeds resulting from thermal pre‐treatment

Abstract: The study has broadened knowledge of the consequences of flaxseed thermal treatment. The deterioration of flaxseed oil oxidative stability is shown. The changes of 19 and 13 kDa proteins suggest their sensitivity to thermally induced aggregation and/or cross-link. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
6
14
0
Order By: Relevance
“…As far as changes in the protein profiles of thermally pre-treated flaxseed samples are concerned, the decrease in the protein fraction at an MW of 13 kDa was noteworthy. A treatment-dependent decrease in this protein fraction was also observed in our previous study on changes in the proteins of a brown flaxseed cultivar (Waszkowiak et al, 2018). As there were similar results in this study, changes in the 13 kDa protein fraction might be characteristic of thermally pre-treated flaxseeds.…”
Section: Protein Profile Of Flaxseed After Thermal Pre-treatmentsupporting
confidence: 91%
“…As far as changes in the protein profiles of thermally pre-treated flaxseed samples are concerned, the decrease in the protein fraction at an MW of 13 kDa was noteworthy. A treatment-dependent decrease in this protein fraction was also observed in our previous study on changes in the proteins of a brown flaxseed cultivar (Waszkowiak et al, 2018). As there were similar results in this study, changes in the 13 kDa protein fraction might be characteristic of thermally pre-treated flaxseeds.…”
Section: Protein Profile Of Flaxseed After Thermal Pre-treatmentsupporting
confidence: 91%
“…The thermal treatment of the flaxseeds was conducted according to the procedure described in detail by Waszkowiak et al [ 28 ]. The parameters were selected on the basis of the previous results [ 25 , 29 , 30 , 33 ] in order to maintain the acceptable sensory quality of roasted flax seeds. The seeds were roasted in a thin layer (3 mm) to achieve homogenous thermal stress.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, heating before cold-pressing of oilseeds generally increases oils yield [ 26 ]. On the other hand, roasting damages the cell structure [ 27 ] and increases the sensitivity of valuable flaxseed compounds to changes induced by thermal treatment [ 28 , 29 , 30 , 31 ]. An earlier study by Waszkowiak, Siger et al [ 28 ] showed that the roasting of flaxseeds at a temperature of 160–220 °C considerably influenced the nutritional quality of flaxseed oil (e.g., the content of total tocopherol decreased, but the content of plastochromanol-8 increased) and deteriorated its oxidative stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seeds are not always preliminarily fried in the production of bread products, so it is advisable to investigate the digestibility of products manufactured with use of flax raw material. In addition, the researcher in [17] found that thermal treatment of flax seeds leads to the deterioration of oxidative stability of seeds fat and extraction of its proteins.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%